THE VITAL ROLE OF MOTIVATION IN LEARNING - Yakubova , Kamola Shokirovna; Rustamova , Nargiza Otabek kizi (Educational Research in Universal Sciences, 2024)
Motivation is often cited as a crucial factor in the learning process. Whether it’s in a classroom setting, workplace environment, or personal development, the role of motivation cannot be overstated. It serves as the driving force behind our actions, influencing our willingness to engage with new information, persist through challenges, and ultimately achieve meaningful learning outcomes. Understanding the intricate relationship between motivation and learning is fundamental to fostering effective educational practices and maximizing human potential.